2015
DOI: 10.7860/jcdr/2015/14893.6427
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acute Painful Thyroiditis with Low Dose Prednisolone: A Study on Patients from Western Nepal

Abstract: IntrOductIOnThyroiditis is defined as a disorder that involves inflammation of the thyroid gland. Thyroiditis is mainly divided into two broad categories: painless and painful. Among the category of painful types of thyroiditis is subacute (de Quervain's thyroiditis) which is the most common cause of acute painful thyroiditis [1]. The patients usually present to the otorhinologists with complaints of neck pain, swelling and odynophagia. On examination, there is tenderness at the region of thyroid gland. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 11 publications
0
20
0
2
Order By: Relevance
“…For Japanese patients, the protocol of 15 mg/day of PSL as the initial dosage for the treatment of SAT was safe and effective [11]. At Pokhara, 20 mg of PSL daily is an adequate treatment of SAT [12]. However, there have been no reports on the optimal dose of PSL for the treatment of SAT.…”
Section: Discussionmentioning
confidence: 99%
“…For Japanese patients, the protocol of 15 mg/day of PSL as the initial dosage for the treatment of SAT was safe and effective [11]. At Pokhara, 20 mg of PSL daily is an adequate treatment of SAT [12]. However, there have been no reports on the optimal dose of PSL for the treatment of SAT.…”
Section: Discussionmentioning
confidence: 99%
“…SAT presents as pyrexia of unknown origin in a patient with human immunodeficiency virus infection. SAT is an uncommon condition that has been treated with either NSAIDs or corticosteroids for many years . Glucocorticoid hormones are important for vital functions and act to modulate inflammatory and immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…SAT is an uncommon condition that has been treated with either NSAIDs or corticosteroids for many years. 12 Glucocorticoid hormones are important for vital functions and act to modulate inflammatory and immune responses. It is often used to treat SAT.…”
Section: Discussionmentioning
confidence: 99%
“…Our patients had received an initial dose of 20 mg of prednisone with a degression as after the first week of treatment. A recent prospective study showed that low dose initial of prednisone (20 mg/j) constituted an adequate and effective treatment of the DQT [11]. The exact duration of the treatment remains nevertheless to be been specified.…”
Section: Discussionmentioning
confidence: 99%